The Impact of Russia-China Trade Relationship on the U.S. Economy - Megits, Nikolay (Journal of Eastern European and Central Asian Research (JEECAR), 2016)
Over the years, bilateral trade between China and Russia experience many turbulences but in recent years has grown rapidly. Their relationship has evolved in such a way that they have come to rely on each other. The reason why Russian-Chinese relationship improved is because of U.S. and EU economic sanctions due to Russian invasion of Crimea and military attacks of Eastern Ukrainian territory. Russia needs China for funding and infrastructure development, and China needs Russia to feed its large energy needs. China and Russia have a strong trade partnership that extends into many different sectors throughout each country. While deep mistrust exists between both sides, China and Russia have proud cultures that desire to be viewed as global powers and believe their relationship with each other will advance that objective. Further, both countries view the West as a hindrance to their overall trade goals, and this marriage of convenience strengthens their position in global affairs which could result in far reaching implications for the world. This paper provides a short overview of how the China-Russia relationship developed, where it is at now, how it could be harmed, and how a stronger trade relationship with the U.S. and rest of the world could subvert those fears. It will also provide recommendations based on a solid foundational understanding of global trade and management.